Pengaruh Fomo Marketing dan Sales Promotion Terhadap Online Impulsive Buying dengan Mediasi Retargeted Advertisements (Studi Pada Mahasiswa FISIP UPN “Veteran” Jawa Timur) - Mainun, Ihtadat Alam Makarima; Azizah, Nurul (Universitas Galuh, 2024)
This research aims to analyze the influence of Fomo Marketing, Sales Promotion, and Retargeted Advertisement on Online Impulsive Buying behavior among Shopee e-commerce users, especially students at the Faculty of Social and Political Sciences, East Java